The inverse of the function f(x) =
is the logarithmic function with base b, denoted as
(x) = log_b(x).
The inverse of the function f(x) =
is the logarithmic function with base b, denoted as
(x) = log_b(x). This means that for any value y,
(y) is the value x such that f(x) = y. In other words, if f(x) =
, then
(y) = x when
= y.
To see why this is true, consider the following equation:
= y
Taking the logarithm of both sides with base b, we get:
log_b(
) = log_b(y)
Since log_b(
) = x, we have:
x = log_b(y)
Therefore,
(y) = log_b(y).